Making rice safe from arsenic. (Research'eu results magazine)
Rice accumulates significantly higher levels of 'arsenic' (As) than other crops. This threat to human health was addressed by EU-funded scientists who conducted risk assessments of 'inorganic arsenic' (i-As) in rice-based products and developed new ways of limiting exposure.